Penguatan Perilaku Pemberian Makan Bayi dan Anak (PMBA) Melalui Pendekatan Emotional Demonstration (EMO-DEMO) sebagai Upaya Pencegahan Stunting - John Amos; Widdefrita; Erick Zicof; Evi Maria Lestari Silaban; Nindy Audia Nadira; Hermita Bus Umar (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2026)
This community service program aimed to improve the knowledge and skills of posyandu cadres as well as enhance the understanding of pregnant women and mothers of children under two years old regarding Infant and Young Child Feeding (IYCF) practices through the Emotional Demonstration (Emo-Demo) approach as an effort to prevent stunting. The implementation method included preparation, participatory-based cadre training, delivery of education using Emo-Demo modules, and evaluation through pre-test and post-test. The results showed a significant increase in cadres’ knowledge, with the average score rising from 49.41 to 77.51. In addition, cadres’ skills in delivering health education improved, and they were able to independently apply the method. The understanding of pregnant women and mothers of young children regarding appropriate IYCF practices also increased. In conclusion, the Emo-Demo approach is effective as a behavior change communication strategy to improve IYCF practices and support the acceleration of stunting prevention at the community level.